Nanocrystal–ligand interactions deciphered: the influence of HSAB and pKa in the case of luminescent ZnO. Issue 3 (27th February 2020) - Champouret, Yohan; Spataro, Grégory; Coppel, Yannick; Gauffre, Fabienne; Kahn, Myrtil L.
Abstract : The p K a values of an organic substrate determines its interaction with the nanocrystal's surface while its hard or soft character will govern the emission intensity of the ZnO nanocrystals. Abstract : Despite all the efforts made by the scientific community to rationalize the interaction of organic molecules with nanocrystals (Ncs), we are still at the level of the empirical recipe when the material behavior in solution is concerned. In an effort to address this issue, the analysis of the luminescence measurements of ZnO Ncs in the presence of various organic substrates using a Langmuir adsorption model was carried out to determine for the first time the affinity constants and the number of binding sites as well as to rank the interaction strengths of these substrates with regard to ZnO Ncs. The results were confirmed by NMR spectroscopic studies, which, besides, provided a deep understanding of the substrate–ZnO Nc interactions. Analysis of the results using p K a and HSAB theory demonstrates that the interaction of a given substrate can be determined by its p K a versus the p K a of the organic molecules present at the surface of pristine Ncs and that the hard or soft character of the substrates can govern the emission intensity of the ZnO Ncs.